Territorial structure of astronomical tourism in the region of Coquimbo, Chile - Páramo Gómez, Juan de Dios (2018)
Astronomical tourism, a segment of the tourism of special interests, made its debut in the international arena just a couple of decades ago. This type of tourism can only be practiced in certain areas of the world where latitude, altitude, climate and the quality of atmosphere contribute to generate the natural conditions specifically needed to observe the celestial dome.  The Norte Chico in Chile is a privileged region in this respect, since its relative location on Earth, the dominant dry climate, as well as the infrastructure available and accessibility to observatories (scientific or otherwise) has given way to the expansion of astronomical tourism in several locations within the Coquimbo region, a part of  Norte Chico.  This paper deals with the issue of territorial structure, a geographical fundamental concept, useful to explaining the expansion of astronomical tourism in this part of Chile.  In doing so, nuclei, flows and surfaces created by this type of tourism economy are revealed.